Chronic and Cumulative Adverse Life Events in Women with Primary Ovarian Insufficiency: An Exploratory Qualitative Study - Sun, Junyan; Fan, Yihui; Guo, Ying; Pan, Huiying; Zhang, Chen; Mao, Guoping; Huang, Yating; Li, Boning; Gu, Tingting; Wang, Lulu; Zhang, Qiuwan; Wang, Qian; et al. (Frontiers in Endocrinology, 2022)
Background and Purpose: Primary ovarian insufficiency (POI) has serious physical and psychological consequences due to estradiol deprivation, leading to increased morbidity and mortality. However, the causes of most POI cases remain unknown. Psychological stress, usually caused by stressful life events, is known to be negatively associated with ovarian function. It is important to explore high-frequency adverse life events among women with POI for future interventions. Methods: Forty-three women (mean age=33·8 years) were recruited who were newly- diagnosed with idiopathic POI (FSH levels >40 IU/L) to participate in semi-structured interviews through convenience sampling. The main questions covered by the topic guide were designed to explore adverse life events prior to POI diagnosis. Interviews were audio recorded, transcribed and analyzed thematically. Data were analyzed from June 2019 to August 2020. Results : Among the women with POI, mean age at diagnosis of POI was 33·8 years (range from 19 to 39 years), and the average time between the onset of irregular menstruation and POI diagnosis was 2.3 years. These women with POI had a relatively normal menstrual cycle before the diagnosis. A number of stressful life events prior to POI diagnosis were discussed by them as important factors influencing their health. Four core themes emerged: 1) persistent exposure to workplace stress, 2) persistent exposure to family-related adverse life events, 3) sleep problem/disturbance existed in women with POI before diagnosis, and 4) participants' general cognition and concerns about POI. Conclusions: Persistent exposures to adverse life events related to work stress, family stress and sleep problem existed in women with POI. Our findings are consistent with the hypothesis that adverse life events play a role in the development of POI. Future research should investigate how social environmental factors influence POI disease risks, and whether provision of tailored interventions (i.e. preventing or mitigating impact of adverse life events) aimed at high-risk populations may help prevent new POI cases and improve conditions of women with POI. We gained an in-depth understanding of the experiences of these women via 1:1 qualitative method, and find adverse life events are frequent in women with POI prior to the diagnosis.